Health Risk Assessment of Some Heavy Metals Pollution in Muscles of Barbus xanthopterus (Heckel, 1843) in Al-Gharraf River Southern of Iraq - Wisam Th. Al-Mayah (Journal of Global Pharma Technology, 2018)
One sampling station was selected to conduct the study in Al-Gharraf River in Kut -Al-Haay city. The samples were taken from the study station at once every month from June of 2017 until May 2018 for year. The study results showed that the mean concentrations heavy metals are vary seasonally in their levels and analyses of muscles indicate that Ni occupied the first position and revealed the highest levels, in general. The minimal recorded accumulative value (0.187ppm) was in spring and the highest (0.251 ppm) in summer. Zinc occupied second accumulation levels and showed the minimal (0.039 ppm) in spring, whereas Cd, by no means, exhibited the minimal concentrations and the lowest value (0.0053 ppm) was in winter.Keywords: Heavy Metals, Fish, Water Pollution, Al-Gharraf River.